The Impact of Economic Changes on Digital Marketing Patterns in the Geotourism Industry of Mazandaran - Hosseinzadeh, Helia; Pourahmad, Ahmad; Ferdowsi, Sajad; L. Warren, Nooshin (Management Strategies and Engineering Sciences, 2025)
The geotourism industry, as a subset of the tourism sector, is significantly influenced by economic changes and digital marketing patterns. This study aims to examine the impact of economic changes on digital marketing patterns in the geotourism industry of Mazandaran Province. This study adopts a descriptive-analytical approach and employs quantitative methods. Data were collected through the distribution of structured questionnaires among 50 experts and practitioners in the tourism industry of Mazandaran. The statistical population included all experts and managers related to the geotourism industry as well as tourists in the region. To analyze the data, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) multi-criteria decision-making model was utilized to assess the extent to which the counties of Mazandaran Province have benefited from economic changes and digital marketing patterns. The results indicated that Neka County, with the highest final score (18113.89) and ranking first, is the most successful county in leveraging economic changes and implementing effective digital marketing strategies. In contrast, Ramsar and Babol counties, ranked 16th and 15th, respectively, face more challenges in this regard. Additionally, Sari, Miandorud, Babolsar, and Fereydunkenar counties were identified as regions with strong potential for attracting tourists. These findings enable decision-makers and geotourism industry practitioners to identify the strengths and weaknesses of each county and formulate more optimal strategies for improving economic conditions and enhancing digital marketing activities. Ultimately, this research can contribute to the sustainable development of the geotourism industry in Mazandaran.